Phenol adsorption from wastewater using cashew nut shells as adsorbent - Kulkarni, Kartik; Sudheer, Varsha; R Girish, C (International Journal of Engineering and Technology, 2018)
The potential of agricultural waste cashew nut shells as an adsorbent for removing phenol from wastewater is presented in this paper. The adsorbent was treated with 3M sulphuric acid in order to improve the properties. The experimental parameters such as adsorbent dosage, concentration and temperature were optimized with response surface methodology (RSM). The isotherm data were tested with different isotherm models and it obeyed Freundlich Isotherm showing the multilayer adsorption. The kinetic data satisfied pseudo-first order kinetic model. The maximum adsorption capacity was calculated to be 35.08 mg/g proving the capability of cashew nut shells for removing phenol from wastewater.Â Â